Grazing Into the Anthropocene or Back to the Future? - Behnke, Roy H. (Frontiers in Sustainable Food Systems, 2021)
This essay examines three central components of extensive livestock production – herd composition, grazing/pasture management, and rangeland tenure. In all of these areas, fenced and open-range forms of migratory pastoralism face a number of shared problems. Set aside the presumption that either one of these systems is technically or institutionally more advanced than the other, and it turns out that each has lessons for the other. For a variety of reasons including climate change, we can look forward to a future world with less grass, which presents a challenge for livestock producers reliant on grass feeding livestock. With little delay and minimal scientific support, East African pastoralists are already adjusting to a new woody world by diversifying the species composition of their herds to include more browsers – camels and goats. There is a potential lesson here for commercial ranchers who have traded the stability of mixed herds for the profitability of keeping sheep or cattle alone. Migratory rangeland systems distribute livestock very differently than fenced, rotational systems of livestock and pasture management. Whereas migratory herds exploit environmental heterogeneity, fenced ranching attempts to suppress it. Emerging archaeological evidence is demonstrating that pastoralists have amplified rangeland heterogeneity for millennia; ecological research shows that this heterogeneity sustains both plant and wildlife biodiversity at the landscape scale; and new approaches to ranch management are appropriating aspects of migratory herding for use on fenced ranches. A rapprochement between the environmental sciences, ranching, and open-range migratory pastoralism has occurred and merits wider policy recognition. In contemporary Africa, indigenous tenure regimes that sustain open rangelands are eroding under pressure from market penetration and state encapsulation. At the same time in the American West, there are emerging novel land tenure instruments that replicate some of the most important functional characteristics of tenure arrangements in pastoral Africa. After many false starts, it appears that some aspects of American ranching do provide an appropriate model for the preservation of the open-range migratory systems that they were once supposed to supplant. ‘Development’ policy needs to reflect upon this inversion of roles and its implications for accommodating diversity.